Effect of strain rate and temperature on deformation and recrystallization behaviour of BCC structure AlCoCrFeNi high entropy alloy. (August 2022) - Arab, Ali; Guo, Yansong; Dilshad Ibrahim Sktani, Zhwan; Chen, Pengwan
Abstract: The mechanical properties and microstructure evolution of AlCoCrFeNi High-Entropy Alloys (HEAs) at different strain rates and temperatures were investigated. High strain rate experiments are performed by the split-Hopkinson pressure bar (SHPB) at strain rates of 500, 1500 and 2500 s −1  at three different temperatures (27, 250 and 500 °C). And Gleeble machine was used to carry out the experiment at high temperatures (500, 750 and 900 °C) under quasi-static compression condition. Stress-strain curves indicated flow stress is increased by raising the strain rate at all temperatures. Microstructure observation of the deformed samples show no any dynamically recrystallized (DRX) occurred at tested condition. However, it is several transgranular cracks are observed in tested samples, the number of the cracks are decreased by rising the temperatures. At temperature higher than the 500 °C under quasi-static condition DRX microstructure with unrecrystallized coarse structure with necklace morphology is observed in deformed sample. The average grain size in the DRX region is around 0.5 μm. It is worth to mention, DRX grains do not show preferred orientations at formed necklace structure. Highlights: Mechanical properties of the AlCoCrFeNi as BCC structure HEA was investigated. Dynamic Behavior of the AlCoCrFeNi was investigated by the SHPB apparatus. High temperature deformation mechanism of the AlCoCrFeNi was studied. Dynamic recrystallization was occurred at high temperature at quasi-static condition. No dynamic recrystallization was observed at high strain loading.